The Effect of Oxytocin Massage by Using Lemongrass Oil (Cymbopogon citratus) Aromatherapy to the Increased of Breast milk Production in Breastfeeding Mothers in Mojo Health Center, Kediri, Indonesia - Susanti Pratamaningtyas; Kekoeh Hardjito; Alfi Rohmatul Hamim (Humanistic Network for Science and Technology (HNST), 2020)
Breast milk is the best food for babies. In the field of midwifery there are several ways to help increase milk production. Oxytocin massage is a massage on both sides of the mothers' limbs to provide stimulation of oxytocin reflex because it gives comfort to mother. Massage using aromatherapy essential oil is useful to anticipate depression because of relaxation effect caused by smells and massage. The purpose of this research is to know the effect of oxytocin massage using lemongrass aromatherapy oil to increase milk production in breastfeeding mothers in Mojo Health Center. This research used comparative research of 2 dependent samples and comparative research of 2 independent samples designs. The sampling technique used was accidental sampling with random allocation of 16 respondents. Based on the Mc Nemar test in the group that was given the oxytocin massage using Serai Lemongrass aromatherapy oil, χ2 counting value was 4,167. Because of χ2 counting value > χ2 table (3.841), this indicated that there was effect of the oxytocin massage using lemongrass aromatherapy oil in the production of breast milk. Keywords: oxytocin massage; lemongrass aromatherapy oil; breast milk; breastfeeding